Cycle Nation: Assessing the Feasibility of Delivering a Multi-Component Cycling Intervention in Two Contrasting Community Settings (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Cycling offers health and environmental benefits, yet levels are low in the United Kingdom (UK). Effective cycling interventions in the community are therefore essential. Cycle Nation (CN) is a 9-week group-based intervention incorporating cycling skills, bicycle maintenance, behaviour change techniques, and provision of equipment. CN was originally rigorously developed as a workplace-based intervention and was adapted for the community setting. The aim of this project was to assess the feasibility of delivering the CN intervention in different community settings.Methods: The CN programme was delivered by local cycling organisations in Manchester with South Asian women and with residents in Glasgow, UK. Participants completed pre- and post-intervention self-report questionnaires including number of cycling rides and minutes per week cycling, cycling confidence and motivation, self-esteem, and vitality. Attendance and programme completion were recorded, and interviews conducted with CN participants and facilitators. Observations were conducted of sessions. Quantitative data were analysed descriptively; qualitative data were analysed thematically.Results: Across the two settings, 49 participants were recruited (n = 19 in Manchester and n = 30 in Glasgow) (40 female, 7 male, and 2 other) and only five withdrew in total. At post-intervention, participants in Manchester reported an increase in cycling by 3.1 rides and 89.3 minutes per week, and participants in Glasgow reported an increase of 5.2 rides and 144.3 minutes per week. In both settings this was mainly attributed to leisure cycling. CN enhanced cycling confidence, motivation for cycling, and self-esteem. In participant interviews, women highlighted the value of group-based cycling sessions, describing them as inspiring and empowering. They reported feeling increased confidence, physical and mental benefits, and higher levels of physical activity.Conclusion: This study demonstrates that delivering CN in community settings is highly feasible and was positively received by participants and facilitators. Cycling levels increased and there was high recruitment and retention rates. Findings suggest CN has potential to be effective in different contexts and can support cycling in underrepresented population sub-groups. Future research will include a randomised controlled trial of CN to provide robust longer-term evidence of its effectiveness and cost-effectiveness, with an embedded process evaluation.Support/Funding Source: Natural Environment Research Council & British Cycling.